Polyomavirus nephropathy: Risk analysis in paired renal Transplant recipients - Esteves, André Barros Albuquerque; Ulisses, Luiz Roberto Sousa; Camargo, Leonardo Figueiredo; Rivelli, Gabriel Giollo; Sousa, Marcos Vinicius de; Mazzali, Marilda (Brazilian Journal of Transplantation, 2016)
Polyomavirus allograft nephropathy (PVAN) has a negative impact on allograft function and survival. Analysis of paired kidneys from same donor can help to understand the role of recipient risk factors for PVAN. This analysis can also define donor related risk factors. Purpose: To identify recipient related risk factors for PVAN. Patients and Methods: Transversal cohort of 24 renal transplant patients in regular outpatient clinic follow up. Twelve patients with PVAN and their paired controls (recipients from same donor) without decoy cells in cytology were included in this analysis. Medical records were analyzed for demographic data, information of transplant and post-transplant data (acute rejection, renal function, immunosuppression). Results: Groups were comparable for initial immunosuppressive therapy based on basiliximab induction, tacrolimus, mycophenolate and steroids. Etiology of end-stage renal disease, race, age, HLA matching and delayed graft function considered as risk factors were also similar between patients with or without PVAN. However, PVAN group had more male patients (91.6 vs. 66.6%, PVAN versus control, p<0.05), higher incidence of biopsy proven acute rejection (41.6% vs. 8.3%, PVAN vs. control, p<0.05) and a trend to shorter cold ischemia time (15.6+6.2 versus 19.7+5.0, p=0.06). Conclusion: In this series, there were no significant differences in immunosuppressive therapy, age and HLA matching between patients with or without PVAN common risk factors. The only factors to be considered in this series were older age and a trend to shorter cold ischemia time in PVAN patients.